Devaluation of cultural capital on online platforms and the changing shape of the social space. (1st January 2020) - Höhne, Thomas; Sproll, Martina
Abstract : This article analyses the devaluation of work and qualifications on crowdworking platforms. It argues that - in the context of a digital reputation economy - cultural capital (formal and incorporated standards of skills and knowledge) is increasingly being devalued, informalised and replaced by symbolic capital. We argue that these changes impact on social relations and the social space. The devaluation and precariousness of crowdwork does not only reflect a crisis of social reproduction and increasing socio-economic inequalities, but also changes traditional channels of upward mobility and thus the structuring of the social space. Furthermore, increasing individual competition implies gendered and discriminatory dynamics.